2023
DOI: 10.1111/pai.13984
|View full text |Cite
|
Sign up to set email alerts
|

Dietary prevention strategies for childhood asthma

Abstract: Asthma is the most common chronic disease in childhood and a rise in prevalence has been observed concomitantly with changing dietary habits in the Western world. This change has favored a more Westernized diet characterized by high intake of processed food and fat in contrast to a Mediterranean diet high in fruit, vegetable and fish intake. This has resulted in a decreased intake of several antioxidants and micronutrients including n‐3 long‐chained polyunsaturated fatty acids and vitamin D that are speculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…In recent years, a growing number of studies have shown that asthma is associated with both dietary factors, highlighting the role of nutrition in its development and management 4 . Among these factors, the intake of n‐3 polyunsaturated fatty acids (PUFAs) has garnered attention because of their diverse biological effects, including anti‐inflammatory and immune‐modulatory properties, which may offer potential benefits for asthma prevention and management 5–7 . N‐3 PUFAs comprise α‐linolenic acid, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a growing number of studies have shown that asthma is associated with both dietary factors, highlighting the role of nutrition in its development and management 4 . Among these factors, the intake of n‐3 polyunsaturated fatty acids (PUFAs) has garnered attention because of their diverse biological effects, including anti‐inflammatory and immune‐modulatory properties, which may offer potential benefits for asthma prevention and management 5–7 . N‐3 PUFAs comprise α‐linolenic acid, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA).…”
Section: Introductionmentioning
confidence: 99%
“…4 Among these factors, the intake of n-3 polyunsaturated fatty acids (PUFAs) has garnered attention because of their diverse biological effects, including anti-inflammatory and immune-modulatory properties, which may offer potential benefits for asthma prevention and management. [5][6][7] N-3 PUFAs comprise α-linolenic acid, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA). Linolenic acid, an essential fatty acid, is predominantly found in foods such as flaxseed oil, walnuts, and soybeans.…”
Section: Introductionmentioning
confidence: 99%
“…
Asthma is the most common chronic disease in childhood, and one‐third of children in western countries report a history of at least one wheezing episode in the first 5 years of life 1 . Childhood asthma is a major public health issue, given its relatively high prevalence, its strong negative impact on the quality of life of both patients and caregivers, and its associated healthcare costs 1 . Recognizing factors predictive of the development of asthma in children may suggest factors that can be intervened upon to reduce this burden 2 …”
mentioning
confidence: 99%
“…Diet also plays a major role in promoting the eventual development of asthma in preschool‐aged children with recurrent wheezing. The adoption of more “Western” diets characterized by a high proportion of processed foods but a low proportion of fruits, vegetables, and healthy oils has been blamed for a significant proportion of the increase in preschool wheeze and asthma 1,8 . Thus, many studies have evaluated the benefits of dietary changes in improving respiratory outcomes in preschool wheezers as highlighted in the review by Brustad N et al.…”
mentioning
confidence: 99%
“…Thus, many studies have evaluated the benefits of dietary changes in improving respiratory outcomes in preschool wheezers as highlighted in the review by Brustad N et al. in this virtual issue 8 . Many macro‐ and micro‐nutrients have been studied but from current evidence, the immunoregulatory benefits of vitamin D supplementation and n‐3 long‐chained polyunsaturated fatty acids (LCPUFAs) supplementation prenatally and early in life offer the greatest opportunities for improving outcomes in preschool wheezers 8 .…”
mentioning
confidence: 99%